DNA metabarcoding in diet studies: Unveiling ecological aspects in aquatic and terrestrial ecosystems. Issue 3 (8th August 2019) - de Sousa, Lara Loureiro; Silva, Sofia Marques; Xavier, Raquel
Abstract: Effective conservation of species and ecosystems requires the understanding of important ecological traits, such as dietary habits, food webs, and trophic niches. In diet studies, the visual identification of partially digested prey has been enhanced with the recent more powerful and accurate technique, DNA barcoding. Here, we summarize the contribution of this recent methodology to the investigation of both terrestrial and aquatic taxa diet, and compare the level of novelty uncovered through the use of this technique regarding species' ecology. From a total of 150 studies analyzed, focusing on more than 250 vertebrate wild species, seven domesticated taxa, and humans, we suggest that barcoding has led to more significant findings for aquatic taxa and ecosystems, where direct observations of feeding events and consequent trophic niche understanding are typically limited. Finally, we introduce the term dietary DNA (dDNA) to describe environmental approaches that use DNA extracted from gut, stomach, or fecal contents, aiming to assess both species dietary habits and describe local biodiversity. Particularly, we highlight the complementarity of environmental DNA (eDNA) and dDNA as a new tool for biodiversity assessments in remote areas, including most of the aquatic realm. Abstract : We reviewed 150 diet studies using molecular barcoding approaches, focusing on more than 250 vertebrates. We discussed the multiple biases existing in current literature (e.g., taxonomic and geographical biases), identified research priorities as well as new venues of research. Specifically, we concluded that although studies using metabarcoding approaches to investigate the diets of aquatic taxa are lagging well behind those on their terrestrial counterparts, the application of this technique to aquatic organisms has fostered more significant findings and dietary paradigms shifts. This is probably due to the fact that the aquatic environment is generally less accessible and direct observations of feeding events, and consequently, trophic webs are less understood.